Learning English Vocabulary for Young Learners' Through Song, Move and Video Methods - Irma Fitriana Harahap; Farida Repelita Waty Kembaren (Jayapangus Press, 2023)
Foundational language abilities, particularly in English, are developed and nurtured throughout early childhood schooling. help get the next generation ready to compete on a global scale. Due to instructors' lack of information regarding effective methods of teaching English to primary school pupils, this research highlights the issue of kids not being exposed to the language at an early age. Activities and songs are used to educate youngsters the English language. With this study, I want to shed light on the ways in which SD Negeri 1 Gunung Tua, located in North Sumatra, use musical and kinetic video technology. This study used a qualitative descriptive research approach to investigate the usage of song, movement, and video using a sample size of twenty fourth-grade children. Young children benefit from singing and dancing together because it helps them develop their English language skills (children acquire English words by singing them), motor skills, and collaborative abilities. This study may help educators create a classroom setting that is conducive to English language acquisition.